SINTESIS KARBON AKTIF CANGKANG JENGKOL (Pithecellobium lobatum) DENGAN BANTUAN ULTRASONIK SEBAGAI BAHAN PENYIMPAN ENERGI ELEKTROKIMIA - Hariati, Hariati; Hindryawati, Noor; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2017)
Research on the synthesis of activated carbon from jengkol shells (Pithecellobium lobatum) with the help of ultrasonic waves as an electrochemical energy storage material has been done. The activated carbon from jengkol shells is characterized by surface area using blue methylene method and pore morphology with SEM (Scanning Electron Microscope) instrument. The characterization results show that the active carbon with ultrasonic wave exposure has a larger surface area of 181.3693 m2/gram than the activated carbon without exposure to ultarsonic waves of 178.0290 m2/gram. The SEM results in activated carbon with ultasonic wave exposure indicate that the pore distribution is more evenly distributed, the number of pores more, and the pore size tends to be smaller, whereas in the activated carbon without the exposure of larger and slightly larger portions of ultrasound waves. The optimum value of capacitance on activated carbon without and with ultrasonic wave exposure of and 6.97 μF/gram and 5.21 μF/gram.